Sejarah Masjid Ciranjang di Kabupaten Cianjur Tahun 1932 – 2020 - Muhamad Iqbal Al Hilal; Agus Permana (UIN Sunan Gunung Djati Bandung, 2022)
The research was conducted to find out the history and development of religious activities in Ciranjang Mosque that have never been reviewed by any researcher, the method used is qualitative method, namely using Heuristics, Interpretation, Criticism, and Historiography, in the results of the study found differences in information between the source and website information the difference is about the year of the establishment of the Mosque that some argue in 1932 and some argue Â 1936. When doing in the field is difficult to find other sources because all the speakers have passed away, it can be concluded that Ciranjang Mosque has a long journey since its establishment in addition to being a center of religious and religious activities but also often used for other important activities.